Analisis Pengaruh Persepsi Keamanan, Kemudahan Transaksi, dan Pengalaman Berbelanja terhadap Minat Pembelian Online Melalui Tokopedia - Pandiangan, Norenty Elisabet; Prayogo, Rangga Restu (ProBisnis : Jurnal Manajemen, 2025)
This study aims to determine the influence of security perception on purchase intention, to determine the influence of ease of transaction on purchase intention, and to determine the influence of shopping experience on online purchase intention through Tokopedia. The sampling technique used was the Accidental Sampling technique, the sample used was 140 student respondents from the State University of Medan who had shopped online at Tokopedia while the analysis tools used were multiple linear regression analysis, classical assumption test, t-test, F-test and coefficient of determination (R2). Based on the results of this study, it is known that the Perception of Security variable (X1) has a positive and significant influence on Purchase Intention (Y), Ease of Transaction (X2) has a positive and significant influence on Purchase Intention (Y), and Shopping Experience (X3) has a positive and significant influence on Purchase Intention (Y). Simultaneously, the three variables, namely Perception of Security (X1), Ease of Transaction (X2), and Shopping Experience (X3) have a positive and significant influence on Online Purchase Intention through Tokopedia.